PENERAPAN LEAN GREEN LOGISTIC MELALUI PENGGUNAAN MEDIA PERTUMBUHAN MIKROBA UJI LABORATORIUM DI PERUSAHAAN FARMASI - Fauziah, Rahmi; Gaol, Indra Nadu Lumban; Firmansyah, Yosep; Fauzi, Muchammad (Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The pharmaceutical industry has a significant environmental impact due to the use of chemicals, energy, and waste production. Microbiology laboratories in the pharmaceutical industry have an important role in testing pharmaceutical products, but the use of specialized microbial growth media in these laboratories produces waste and has an impact on the environment. Lean Green Logistics, which focuses on reducing waste in the supply chain while minimizing environmental impact, is a potential solution in addressing this problem. By identifying waste reduction opportunities, such as inventory to be more efficient, this research aims to reduce waste, reduce environmental impact, and lower operational costs. The calculation results show that the use of smaller petri dishes reduces the use of R2A media by 40%, in addition to reducing the cost of the media used, the waste produced is also reduced. This reflects the principles of Green Logistics and the application of Lean Management in reducing inventory wastage, thus helping pharmaceutical companies in optimizing procurement logistics.